You are on page 1of 6

# (0 1)

.
x

0
0
1
1

0
1
0
1

n
2n.

1
0
1
1

1
0
1
1

, .. .
x

x yz

x+y+z

x yz

x+y+z

xy z

x+y+z

xyz

x+y+z

x yz

x+y+z

x yz

x+y+z

x+y+z

xy z
xyz

x+y+z

1= xy z + xyz + x y z + x yz + xyz ( )
1= ( x + y + z )( x + y + z )( x + y + z ) ( . )

a) f n , f(x1, x2, , xn),
n , :
(1)

(2)

## x 1 f(0, x2, , xn)

a 0 x 1 x 2 L x n + a 1 x 1 x 2 L x n 1 x n + L + a 2n 2 x 1 x 2 L x n + a 2 n 1 x 1 x 2 L x n

n , :
(1)

(2)

## + x )L( b n + x1+ x 2 +L+ x n )( b n + x1+ x 2 +L+ x n )

f(x1, x2, , xn)= ( b0 + x 1 + x 2 +L+ x n )( b1+ x +L+ x
2 2
2 1
1
n 1 n

..
. -.

1.

(XOR) [xy] 1
x y , 0 .
: xy =

2.

xy + x y

(NAND) e (AND)
:

3.

xy = x + y

(NOR) e (OR)
:

4.

( x + y) = x y

(XNOR) e (XOR).
:

x y = xy + x y = xy + x y

XOR

NAND

NOR

XNOR

xy

xy

x+y

xy

0
0
1
1

0
1
0
1

0
1
1
0

0
0
1
1

0
1
0
1

1
1
1
0

0
0
1
1

0
1
0
1

1
0
0
0

0
0
1
1

0
1
0
1

1
0
0
1

, ()
.
(1) {AND, OR NOT} .
(2) xy = ( x + y) ( => {OR
NOT} .
(3) x + y = ( x y) ( =>
{AND NOT} .
(4)

a) x = x + x = x x ( )

( )( )

{NAND}

) x y = x y = x y x y ( )
(5) {NOR}

..
. -.

()

1. (NOT) -

x
y

3. (OR)

x
y

x+y

5. (OR)

x
y

2. (AND)

xy
4. (NAND)

x
y

xy

6. (XOR)

x+y

xy

:
.1 :
) x y = x y
) x y = x y
) xy x y = x y

()
() () () ()
) x y = (x )y + x (y ) = x y + xy = xy + x y = x y
) xy x y = (xy )(x y ) + (xy )(x y ) = (x + y )(x y ) + (xy )(x + y ) =

) x y = x y + x y = xy + x y = x y + x y = x y + x y = x y

= x y + xy = xy + x y = x y

.2 - (XOR) :
) (NAND)
) (NOR)

( ) ( ) ( )( )

) x y = xy + x y = xy + x y = xy x y

) x y = xy + x y = ( xy + x )( xy + y) = ( x + x )( y + x )( x + y)( y + y) = ( x + y)( x + y) = (x + y ) + x + y

..
. -.

.3
(x y ) z = x (y z)

(XOR)

..

## (x y ) z = (xy + x y ) z = (xy + x y )z + (xy + x y )z = (x + y )(x + y )z + (xy + x y )z =

) (

= x x + xy + y x + yy z + xy + x y z = xyz + y xz + xy z + x y z =
= xyz + x yz + xyz + x yz = x ( yz + y z) + x ( yz + yz) =

( )

## = x ( yz + yz) + x ( yz + y z) = x ((yz) y z ) + x ( yz + yz) =

= x ( y + z (y + z )) + x ( yz + yz) =

(
)
= x (yz + yz ) + x ( yz + y z) =

= x yy + yz + yz + z z + x ( yz + yz) =
= x ( yz + y z) =
= x (y z)
.4 :

) {NOR ()}
) {NAND ()}
.

:
)

{NOR} - NOR

, (, +,

):

1. x = (x + x )

) (

2. x y = (x y ) = x + y = (x + x ) + (y + y )
3. x + y = (x + y ) = (x + y ) + (x + y )

, ( )
NOR => NOR .
)

{NAND} - NAND

, (, +,

):

1. x = (x x )
2. x y = (x y ) = (x y ) (x y )

( ) (

3. x + y = (x + y ) = x y = x x y y

, ( )
NAND => NAND .

..
. -.

.5 :
) A B + AC + BC

) x y + y + z (x + z )
:
1. (AND) (NOT)
2. (NOR)
3. (NAND)

:
)

1 {AND, NOT}

( )

( )

A B + AC + BC = A B + AC + BC = A B (AC) BC
2 {NOR}

( )
( ) ( )( )( )

## = {[(A + B) + (A + C ) (B + C )] 1}== [(A + A + B) + ((A + A ) + (C + C )) + (B + (C + C ))] + 0

A B + AC + BC = A B + AC + BC = A B (AC) BC = A + B A + C B + C

3 {NAND}

( )

( ) [(

A B + AC + BC = A B + AC + BC = A B (AC) BC = A (B B) (AC) (B B) C
)

1 {AND, NOT}

( )

)]

( ) ( ) ( ) [( ) ( )]

x y + y + z (x + z ) = x y + y + z (x + z ) = x y + yz + x z = x y + yz x z = x y yz x z
2 {NOR}

( )

x y + y + z (x + z ) = x y + y + z (x + z ) = x + y + y + z + (x + z ) =

x + y + y + z + (x + z ) 1 = x + x + y + y + (z + z ) + (x + z ) + 0

3 {NAND}

( )
(( ) ( )) (

## = (x y ) [(y z ) (x z )] = (x (y y )) [((y y ) z ) ((x x ) (z z ))]

( ) ( ))

x y + y + z (x + z ) = x y + y + z (x + z ) = x y + y z + x z = x y + y z x z

.6 NAND () :
:

,
.

..
. -.

x+y=xy

.7 NOR () :
:
,
.

xy=x+y

.8 (XOR)
.

: ,

, +
.

F = x y = xy + x y

( )( )
= (x x + xy + x y + y y ) = (xy + x y ) = F

( ) (

Fd = x + y x + y = x x + xy + x y + y y = xy + x y = xy x y = x + y ( x + y) =

.9 B. B ,

3 () . 1 s,
2 s. () 1,
0. :
B z.

B
z

..
. -.

3 s
2 s

2 s